Ionic conductivity studies of LiCF3SO3 doped hexanoyl-chitosan polymer films - Tan Winie; A.K. Arof (Institut Teknologi Bandung, 2004)
Hexanoyl-chitosan that exhibited solubility in THF was prepared by acyl modification of chitosan. Films of hexanoyl-chitosan containing LiCF3SO3 were prepared by the solution cast technique. Complexation of the prepared electrolytes was studied by FTIR analysis. For the system containing 30 wt.% LiCF3SO3 salt, the room temperature conductivity achieved was 6.03 x 10-7 S cm-1 and with the addition of 30 wt.% EC to this system, the conductivity was enhanced to 2.75 x 10-5 S cm-1. The variations in conductivity at room temperature are explained by the Rice and Roth model from which the density of mobile ions, mobility of ions and diffusion coefficient were obtained.